Streptomyces tamarix sp. nov.: antagonism against Alternaria gaisen producing streptochlorin, isolated from Tamarix root soil - Chen, Yi-huang; Wu, Yi Zheng; Liu, Qin; Xia, Zhanfeng; Wang, JianMing; Luo, Xiao-Xia (Frontiers in Microbiology, 2023)
By the end of 2021, the pear yield in Xinjiang has reached 1,795,900 tons, accounting for 1/9 of the country. Alternaria gaisen disease caused by pear black spot seriously touching the pear industry. Alternaria gaisen can infect almost all pear. Alternaria gaisen caused a black spot on the pear,which adversely impacted the yield and quality of fruit. In this study, The strain TRM76323 of Streptomyces has a level of high antagonistic activity against Alternaria. It was isolated from the soil of the Tamarix chinensis in Xinjiang Province. In this study, it used a multiphase classification and identification method was used to identify the genetic classification status of the antagonistic strains. Based on modern isolation and purification identification techniques, the antibacterial active components of Streptochlorin were identified, and the antagonistic activity of Streptomyces against Alternaria was analyzed through in vitro and in vivo experiments. This study enhanced the resource bank of antagonistic microorganisms in extreme environments in Xinjiang, identified the active components, and improved the bank of drug lead compounds further. This study demonstrated a new idea for the prevention and control of pear black spot disease.